ANALISA HAK WARIS ANAK LUAR KAWIN PENDEKATAN HAK ASASI ANAK - Achmad Fageh (Universitas Islam Lamongan, 2017)
the principle of children's rights, and the principles and evidence nasab nasab purification, has put the construction of a biological child rights and child relationship with the biological father of the biological structure that can not be a permanent relationship can shift under any circumstances. It is based on the purification of biological relationship status as a relationship that is both natural (nature), and by repositioning the child into the concept of nature that puts the child's position as the mandate of God who have the same rights and status as a legitimate child.Keywords : principle of children's rights and inheritance rights Illegitimacy.